Analisa Below The Line Dan Store Atmosphere Terhadap Impulse Buying Dan Emosi Positif Sebagai Variabel Intervening Pada Indomaret Di Kota Semarang. - Camilus Isidorus Ikut; Hasyim Hasyim (Universitas Veteran Bangun Nusantara, 2023)
This research is motivated by the increasing choice of retail stores nowadays, making retail entrepreneurs have to compete to attract consumer interest. This research was conducted to analyze the influence of Below The Line and Store Atmosphere on Impulse Buying and Positive Emotions as Intervening Variables for Indomart, Semarang City. In this research, the author uses below the line and Store Atmosphere as independent variables that will be examined for their influence on impulse buying, as well as positive emotions as an intervening variable for their influence on impulse buying. This research was conducted by distributing questionnaires to 100 consumers. The sample for this research was determined using accidental sampling technique. Analysis of the data obtained is in the form of qualitative and descriptive analysis. Quantitative analysis includes validity and reliability tests, normality tests, classical assumption tests (multicollinearity test, heteroscedasticity test), multiple linear regression analysis, hypothesis testing via the coefficient of determination, F test and t test. The results of the t test show that each of the below the line and Store Atmosphere variables partially and significantly influences the positive emotion impulse buying variable. and the positive emotion variable has a significant and influential effect on the impulse buying variable. Furthermore, with path analysis, the below the line variable has a direct and significant effect on the impulse buying variable. Meanwhile, the Store Atmosphere variable does not have a direct and significant effect on the impulse buying variable.